Preparation method of nylon / polyester compatilizer
By grafting the anhydride groups on the copolymer of nylon and polyester, a nylon/polyester compatibility problem was solved, and the performance and cost-effectiveness of the composite material were significantly improved.
Patent Information
- Application Number
- CN202411857939.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
Due to the differences in molecular structure and poor compatibility of nylon and polyester, their applications in the field of engineering plastics are limited.
By grafting the highly active anhydride group onto the copolymer of acrylamide, a nylon/polyester compatibility is prepared to enhance the capacity enhancement effect of nylon and polyester and the adhesion of the two-phase interface.
It significantly improves the compatibility of nylon and polyester, improves the comprehensive performance of composite materials, including tensile strength, bending strength and impact strength, and reduces production costs.
Smart Images

Figure BDA0005192391780000051 
Figure BDA0005192391780000071 
Figure BDA0005192391780000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic polymer synthesis, and in particular to a method for preparing a nylon / polyester compatibilizer. Background Art
[0002] Amide, commonly known as nylon, has excellent thermal and mechanical properties, wear resistance, self-lubrication, corrosion resistance and easy molding and processing. It is a widely used engineering plastic. However, it also has the disadvantages of strong hygroscopicity, dimensional instability, large molding shrinkage and high cost, so it is necessary to modify it. Polyester has the advantages of high rigidity, good creep resistance, good dimensional stability and low cost, but it also has the problem that its impact resistance, wear resistance and antistatic properties are not as good as nylon. If the advantages of the two polymers can be combined, introducing some polyester resin as a matrix in nylon materials and nylon / glass fiber composite materials can not only improve the crystallization properties and mechanical properties to a certain extent, but also reduce the cost of composite materials and enrich their applications in the field of engineering plastics. However, due to the influence of the molecular structure of the two, nylon and polyester are not compatible. In order to solve the problem of incompatibility between nylon and polyester, a catalyst is usually added to the melt blending system to promote the ester-amide exchange reaction to generate a compatibilizer. For example, patent CN113773508A discloses a polyester / nylon composite material, and its preparation method is to modify the polyester by grafting a sulfonate compound onto the polyester macromolecule so that it undergoes an ester exchange reaction with nylon, thereby enhancing the compatibility of the two. However, it is not only time-consuming but also difficult to achieve industrial production. Summary of the invention
[0003] In order to solve the problem of poor compatibility between nylon and polyester mentioned in the above background technology, a compatibilizer is prepared which can significantly improve the compatibility between nylon and polyester in a short time, improve the comprehensive performance of the alloy, and enable it to be applied in the field of engineering plastics. The present invention provides a nylon / polyester compatibilizer and a preparation method, in which an acid anhydride group with strong activity is grafted onto the main chain to achieve the volume-increasing effect of nylon and polyester and the adhesion of the two-phase interface, thereby improving the uniformity of the mixture.
[0004] The specific technical scheme of the present invention is: a nylon / polyester compatibilizer and a preparation method thereof, comprising the following steps: 1) emulsion copolymerizing propylene (PP), acrylamide (AM), azobisisobutyronitrile (AIBN), an emulsifier and water, purifying and drying to obtain a copolymer of propylene and acrylamide (PPAM), wherein the molar ratio of propylene to acrylamide monomers is 1.2:1 to 1.5:1; 2) subjecting maleic anhydride monomer (MAH), the copolymer of propylene and acrylamide obtained in step 1), benzoyl peroxide (BP) and toluene (MB) to solution polymerization grafting, followed by purification and drying to obtain PPAM-g-MAH, wherein the molar ratio of the copolymer of propylene and acrylamide to the maleic anhydride monomer is 4.2:1 to 5.0:1.
[0005] The present invention first uses PP and AM as monomers and adopts emulsion polymerization to copolymerize and prepare PPAM. The reaction equation is: Then, the MAH monomer was grafted onto PPAM by solution polymerization to prepare PPAM-g-MAH. The reaction equation is: Compared with the single PP polymer, the copolymerization of PP and AM introduces an amide group into the PPAM product, which can form a hydrogen bond with the nylon resin matrix. At the same time, the polar MAH monomer is grafted on the PPAM main chain. Due to the strong activity of the anhydride group, it is easy to react chemically with functional groups such as carboxyl and amine to generate a new structure, which improves the compatibilization effect of nylon and polyester, enhances the adhesion of the two-phase interface, improves the uniformity of the mixture, reduces the size of the dispersed phase, and enhances the adhesion of the two-phase interface. In addition, it can also improve the adhesion between the resin matrix and inorganic fillers such as glass fiber, so that the tensile strength, bending strength, impact strength, etc. of the composite material are significantly improved.
[0006] Preferably, the M of PPAM-g-MAH w It is 6000 to 8000.
[0007] Preferably, the grafting rate of the MAH monomer is 7.1 to 7.8%.
[0008] Furthermore, in step 1), the amount of azobisisobutyronitrile added is 0.4% to 0.6% of the total mass of propylene and acrylamide.
[0009] Furthermore, in step 1), the emulsifiers are sodium dodecyl sulfate and polyoxyethylene octylphenol ether-10, the mass ratio of sodium dodecyl sulfate (SDS) and polyoxyethylene octylphenol ether-10 (OP-10) is 4-4.5:1, and the amount of the emulsifier added is 18-22% of the total mass of propylene and acrylamide monomers.
[0010] Furthermore, in step 1), the amount of water added is 180-200% of the total mass of propylene and acrylamide monomers.
[0011] Furthermore, in step 1), the reaction temperature of the emulsion copolymerization is 55-65° C., and the reaction time is 1-2 h.
[0012] Furthermore, in step 1), the protective gas during emulsion polymerization is nitrogen or carbon dioxide.
[0013] Preferably, in step 1), n-hexane is selected for purification.
[0014] Preferably, in step 1), the drying temperature is 60-80° C. and the drying time is 6-8 hours.
[0015] Preferably, in step 1), during the emulsion polymerization reaction, stirring is performed uniformly throughout the entire process.
[0016] Furthermore, in step 2), the amount of benzoyl peroxide added is 0.8-1.0% of the total mass of the propylene and acrylamide copolymer and the maleic anhydride monomer.
[0017] Furthermore, in step 2), the amount of toluene added is 180-200% of the total mass of the propylene and acrylamide copolymer and the maleic anhydride monomer.
[0018] Furthermore, in step 2), the temperature of solution polymerization grafting is 110-120° C., and the reaction time is 2-3 hours.
[0019] Furthermore, in step 2), the protective gas during solution polymerization grafting is nitrogen or carbon dioxide.
[0020] Preferably, in step 2), during solution polymerization grafting, stirring is performed uniformly throughout the entire process.
[0021] Preferably, in step 2), n-hexane is selected for purification.
[0022] Preferably, in step 2), the drying temperature is 80-90° C. and the drying time is 8-12 h.
[0023] Preferably, the nylon is one of PA6, PA66 or PA10.
[0024] Preferably, the polyester is one of PET, PTT or PBT.
[0025] Preferably, the amount of the compatibilizer is 2% to 5% of the total amount of the matrix.
[0026] Compared with the prior art, the beneficial effects of the present invention are: 1) The nylon / polyester compatibilizer provided by the present invention has a long-chain structure of a copolymer of propylene and acrylamide. The long-chain structure is not only conducive to improving the physical entanglement ability of the compatibilizer with nylon and polyester, but also has a polar amide group, which enables it to generate hydrogen bonds with nylon.
[0027] 2) Compared with conventional compatibilizers, the compatibilizer prepared by the present invention has the advantages of simple process, high grafting rate and low production cost.
[0028] 3) The compatibilizer prepared by the present invention not only has good linking ability with the polyester and nylon in the matrix to reduce the stratification phenomenon, but also can be linked with inorganic additives such as glass fiber, thereby helping to improve the uniformity of the mixture, give full play to the respective advantages of the matrix and the additive, enhance the performance of the composite material, and broaden the application field. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Overall embodiment 1) Preparation of PPAM-g-MAH (1) Emulsion polymerization PP and AM monomers with a molar ratio of 1.2:1 to 1.5:1, 0.4 to 0.6% of the total weight of the monomers as an AIBN initiator, 18 to 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 4 to 4.5:1), and 180 to 200% of the total weight of the monomers as distilled water are respectively added into a three-necked flask, and reacted for 1.0 to 2.0 hours in a nitrogen or carbon dioxide atmosphere at 55 to 65° C.; then, excess n-hexane is used to remove the remaining monomers in the reaction product, and the product is dried at a temperature of 60 to 80° C. for 6.0 to 8.0 hours to obtain PPAM.
[0031] (2) Solution polymerization PPAM and MAH monomers with a molar ratio of 4.2 to 5.0:1 and toluene accounting for 180 to 200% of the total weight of the monomers are respectively dissolved in a round-bottom flask, and a BP initiator accounting for 0.8 to 1.0% of the total weight of the monomers is added, and the mixture is reacted for 2.0 to 3.0 hours in a nitrogen or carbon dioxide atmosphere at 110 to 120° C.; then, excess n-hexane is used to remove the remaining monomers in the reaction product, and the product is dried at a temperature of 80 to 90° C. for 8.0 to 12.0 hours to finally obtain PPAM-g-MAH.
[0032] 2) Preparation of injection molding specimens Prepare a mixture of nylon, polyester and nylon / polyester compatibilizer by mass fraction, taking 60-62 parts of nylon, 36-38 parts of polyester and 2-4 parts of nylon / polyester compatibilizer PPAM-g-MAH prepared in step 2). Dry the uniformly blended mixture at a temperature of 100-105°C for 6-8h.
[0033] The dried mixture is blended and granulated at a temperature of 255-265° C. using a twin-screw extruder, and injection-molded at a pressure of 50-80 MPa and a temperature of 250-260° C. using an injection molding machine to prepare injection-molded strips, wherein the nylon is one of PA6, PA66 or PA10; and the polyester is one of PET, PTT or PBT.
[0034] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0035] Specific examples and comparative examples.
[0036] Example 1 1) Preparation of PPAM-g-MAH (1) Emulsion polymerization PP and AM monomers with a molar ratio of 1.2:1.0, 0.4% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 2.0 h in a nitrogen atmosphere at 55°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 60°C for 8.0 h to obtain PPAM.
[0037] (2) Solution polymerization PPAM and MAH monomers with a molar ratio of 4.2:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.8% of the total weight of the monomers was added, and the mixture was reacted for 3.0 h in a nitrogen atmosphere at 110°C. Excess n-hexane was then used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80°C for 12.0 h to obtain M w The PPAM-g-MAH is 8000 and the grafting rate of MAH is 7.8%.
[0038] 2) Preparation of injection molding specimens Prepare a mixture of nylon, polyester and nylon / polyester compatibilizer by mass fraction, and take 60 parts of nylon 6 (PA6), 36 parts of polyethylene terephthalate (PET) and 4 parts of the nylon / polyester compatibilizer prepared in step 1). Dry the uniformly blended mixture at 105°C for 8 hours.
[0039] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 50 MPa and a temperature of 260° C. using an injection molding machine to prepare injection-molded specimens.
[0040] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 2), no compatibilizer is added, and the rest of the process is the same as that of Example 1. The specific steps are as follows: 1) Preparation of injection molding specimens Nylon and polyester were prepared according to the mass fractions. 60 parts of nylon 6 (PA6) and 36 parts of polyethylene terephthalate (PET) were mixed respectively, and the uniformly blended mixture was dried at a temperature of 105° C. for 8 hours.
[0042] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 50 MPa and a temperature of 260° C. using an injection molding machine to prepare injection-molded specimens.
[0043] 2) Performance Testing The injection molded specimens prepared in step 1) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0044] Table 1 Effect of compatibilizer on the mechanical properties of the final material.
[0045] From the data in Table 1, it can be concluded that the use of the nylon / polyester compatibilizer of the present invention can improve the mechanical properties of the tensile strength, bending strength and notched impact strength of the injection molded spline finally formed. The reason is presumed to be: the nylon / polyester compatibilizer prepared by the present invention has a long-chain structure of propylene and acrylamide copolymer, and the long-chain structure is not only conducive to improving the physical entanglement ability of the compatibilizer with nylon and polyester, but also because it has an amide polar group, it can generate hydrogen bonds with nylon. At the same time, the compatibilizer has good linking ability with the polyester and nylon in the matrix, reducing the stratification phenomenon, and can also be linked with inorganic additives such as glass fiber, which is conducive to improving the uniformity of the mixture, giving full play to the respective advantages of the matrix and the additive, improving the performance of the composite material, and broadening its application field.
[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that in step 1), the molar ratio of PP and AM monomers added is 1.0:1.2, and the rest of the process is the same as Example 1. The specific steps are: 1) Preparation of PPAM-g-MAH (1) Emulsion polymerization PP and AM monomers with a molar ratio of 1.0:1.2, 0.4% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 2.0 h in a nitrogen atmosphere at 55°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 60°C for 8.0 h to obtain PPAM.
[0047] (2) Solution polymerization PPAM and MAH monomers with a molar ratio of 4.2:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.8% of the total weight of the monomers was added, and the mixture was reacted for 3.0 h in a nitrogen atmosphere at 110°C. Excess n-hexane was then used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80°C for 12.0 h to obtain M w The PPAM-g-MAH is 6000 and the grafting rate of MAH is 7.4%.
[0048] 2) Preparation of injection molding specimens A mixture of nylon, polyester and nylon / polyester compatibilizer was prepared by mass fraction, and 62 parts of nylon 6 (PA6), 36 parts of polyethylene terephthalate (PET) and 2 parts of the nylon / polyester compatibilizer prepared in Example 1 were taken respectively. The uniformly blended mixture was dried at a temperature of 100° C. for 6 hours.
[0049] The dried mixture was blended and granulated at a temperature of 265° C. using a twin-screw extruder, and injection-molded at a pressure of 80 MPa and a temperature of 250° C. using an injection molding machine to prepare injection-molded specimens.
[0050] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the molar ratio of PP and AM monomers added in step 1) is 2.0:1.0, and the rest of the process is the same as Example 1. The specific steps are: 1) Preparation of PPAM-g-MAH PP and AM monomers with a molar ratio of 2.0:1.0, 0.4% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 2.0 h in a nitrogen atmosphere at 55°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 60°C for 8.0 h to obtain PPAM.
[0052] PPAM and MAH monomers with a molar ratio of 4.2:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.8% of the total weight of the monomers was added, and the mixture was reacted for 3.0 h in a nitrogen atmosphere at 110°C. Excess n-hexane was then used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80°C for 12.0 h to obtain M w The PPAM-g-MAH is 8300 and the grafting rate of MAH is 7.1%.
[0053] 2) Preparation of injection molding specimens A mixture of nylon, polyester and nylon / polyester compatibilizer was prepared by mass fraction, and 60 parts of nylon 6 (PA6), 38 parts of polyethylene terephthalate (PET) and 2 parts of the nylon / polyester compatibilizer prepared in Example 1 were taken respectively. The uniformly blended mixture was dried at a temperature of 100° C. for 12 hours.
[0054] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 60 MPa and a temperature of 255° C. using an injection molding machine to prepare injection-molded specimens.
[0055] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0056] Table 2 Effect of PP and AM monomer addition on the final material properties From the data in Table 2, it can be concluded that too high or too low an amount of AM monomer added will reduce the tensile strength, flexural strength and notched impact strength of the final injection molded strip. The reason is speculated to be: when the amount of AM monomer added is too high, the AM of the synthesized PPAM w This also leads to the M wWhen the molecular weight of the compatibilizer is too low, its ability to entangle with the matrix macromolecules is also weak, and its ability to combine with the nylon and polyester matrix is not high, resulting in limited improvement in the mechanical properties of the composite material. On the contrary, when the addition amount of AM monomer is too low, due to the high proportion of PP, the M of PPAM is w Too high, which makes the M of PPAM-g-MAH w It is too high, and at the same time, the proportion of amide groups on the matrix is small, and the grafting rate of MAH is low, which is not conducive to the bonding of the compatibilizer with the nylon and polyester matrix, which also leads to low mechanical properties of the composite material.
[0057] Comparative Example 4 The difference between this comparative example and Example 1 is that the molar ratio of PPAM and MAH monomers added in step 1) is 2.0:1.0, and the rest of the process is the same as Example 1, and the specific steps are as follows: 1) Preparation of PPAM-g-MAH PP and AM monomers with a molar ratio of 1.2:1.0, 0.4% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 2.0 h in a nitrogen atmosphere at 55°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 60°C for 8.0 h to obtain PPAM.
[0058] PPAM and MAH monomers with a molar ratio of 2.0:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.8% of the total weight of the monomers was added, and the mixture was reacted for 3.0 h in a nitrogen atmosphere at 110°C. Then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80°C for 12.0 h to obtain M w The PPAM-g-MAH is 8600 and the grafting rate of MAH is 8.1%.
[0059] 2) Preparation of injection molding specimens Prepare a mixture of nylon, polyester and nylon / polyester compatibilizer by mass fraction, and take 60 parts of nylon 6 (PA6), 36 parts of polyethylene terephthalate (PET) and 4 parts of the nylon / polyester compatibilizer prepared in step 1). Dry the uniformly blended mixture at 105°C for 8 hours.
[0060] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 50 MPa and a temperature of 260° C. using an injection molding machine to prepare injection-molded specimens.
[0061] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0062] Comparative Example 5 The difference between this comparative example and Example 1 is that the molar ratio of PPAM and MAH monomers added in step 1) is 10.0:1.0, and the rest of the process is the same as Example 1, and the specific steps are: 1) Preparation of PPAM-g-MAH PP and AM monomers with a molar ratio of 1.2:1.0, 0.4% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 2.0 h in a nitrogen atmosphere at 55°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 60°C for 8.0 h to obtain PPAM.
[0063] PPAM and MAH monomers with a molar ratio of 10.0:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.8% of the total weight of the monomers was added, and the mixture was reacted for 3.0 h in a nitrogen atmosphere at 110°C. Excess n-hexane was then used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80°C for 12.0 h to obtain M w The PPAM-g-MAH is 6400 and the grafting rate of MAH is 6.2%.
[0064] 2) Preparation of injection molding specimens Prepare a mixture of nylon, polyester and nylon / polyester compatibilizer by mass fraction, and take 60 parts of nylon 6 (PA6), 36 parts of polyethylene terephthalate (PET) and 4 parts of the nylon / polyester compatibilizer prepared in step 1). Dry the uniformly blended mixture at 105°C for 8 hours.
[0065] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 50 MPa and a temperature of 260° C. using an injection molding machine to prepare injection-molded specimens.
[0066] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0067] Table 3 Effect of PPAM and MAH monomer addition on the final material properties From the data in Table 3, it can be concluded that too high or too low addition of MAH monomer will reduce the tensile strength, flexural strength and notched impact strength of the final injection molded strip. The reason is speculated to be: when the addition amount of MAH monomer is too high, although the M w The grafting rate of MAH is also high, but due to the high content of side groups, the flexibility of the macromolecular chain is not good, and the entanglement ability with nylon and polyester matrix is not good, which also affects the provision of mechanical properties of the material. When the addition amount of MAH monomer is too low, it not only leads to the M w becomes lower, and the grafting rate of MAH is not high, and there are fewer active sites on the compatibilizer macromolecules, which is not conducive to improving the mechanical properties of the composite material.
[0068] Example 2 1) Preparation of PPAM-g-MAH (1) Emulsion polymerization PP and AM monomers with a molar ratio of 1.3:1.0, 0.5% of the total weight of the monomers as AIBN initiator, 20% of the total weight of the monomers as emulsifiers SDS and OP-10 (the mass ratio of SDS and OP-10 is 80:20) and 180% of the total weight of the monomers as distilled water were added into a three-necked flask, and reacted for 1.5 hours under a nitrogen atmosphere at 60°C; then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the product was dried at 70°C for 7.0 hours to obtain PPAM.
[0069] (2) Solution polymerization PPAM and MAH monomers with a molar ratio of 4.5:1.0 and toluene accounting for 200% of the total weight of the monomers were dissolved in a round-bottom flask, and BP initiator accounting for 0.9% of the total weight of the monomers was added, and the mixture was reacted for 2.5 h in a nitrogen atmosphere at 115 ° C. Then, excess n-hexane was used to remove the remaining monomers in the reaction product, and the reaction product was dried at 80 ° C for 120.0 h to obtain M w The PPAM-g-MAH is 7300 and the grafting rate of MAH is 7.4%.
[0070] 2) Preparation of injection molding specimens Prepare a mixture of nylon, polyester and nylon / polyester compatibilizer by mass fraction, and take 60 parts of nylon 6 (PA6), 36 parts of polyethylene terephthalate (PET) and 4 parts of the nylon / polyester compatibilizer prepared in step 1). Dry the uniformly blended mixture at 105°C for 8 hours.
[0071] The dried mixture was blended and granulated at a temperature of 255° C. using a twin-screw extruder, and injection-molded at a pressure of 50 MPa and a temperature of 260° C. using an injection molding machine to prepare injection-molded specimens.
[0072] 3) Performance testing The injection molded specimens prepared in step 2) were subjected to mechanical property tests of tensile strength, flexural strength and notched impact strength.
[0073] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0074] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a nylon / polyester compatibilizer, characterized in that: The following steps are involved: 1) Propylene, acrylamide, azobisisobutyronitrile, an emulsifier and water are subjected to emulsion copolymerization, and a copolymer of propylene and acrylamide is obtained after purification and drying, wherein the molar ratio of propylene to acrylamide monomers is 1.2:1-1.5:1; 2) The maleic anhydride monomer, the copolymer of propylene and acrylamide obtained in step 1), benzoyl peroxide and toluene are subjected to solution polymerization grafting, and then purified and dried to obtain PPAM-g-MAH, wherein the molar ratio of the copolymer of propylene and acrylamide to the maleic anhydride monomer is 4.2:1-5.0:
1.
2. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 1), the amount of azobisisobutyronitrile added is 0.4% to 0.6% of the total mass of propylene and acrylamide.
3. The method for preparing a nylon / polyester compatibilizer according to claim 1 or 2, characterized in that: In step 1), the emulsifiers are sodium dodecyl sulfate and polyoxyethylene octylphenol ether-10, the mass ratio of sodium dodecyl sulfate and polyoxyethylene octylphenol ether-10 is 4-4.5:1, and the amount of the emulsifier added is 18-22% of the total mass of propylene and acrylamide monomers.
4. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 1), the amount of water added is 180-200% of the total mass of propylene and acrylamide monomers.
5. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 1), the reaction temperature of the emulsion copolymerization is 55-65°C, and the reaction time is 1-2h.
6. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 1), the protective gas during emulsion polymerization is nitrogen or carbon dioxide.
7. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 2), the amount of benzoyl peroxide added is 0.8-1.0% of the total mass of the copolymer of propylene and acrylamide and the maleic anhydride monomer.
8. The method for preparing a nylon / polyester compatibilizer according to claim 1 or 7, characterized in that: In step 2), the amount of toluene added is 180-200% of the total mass of the propylene and acrylamide copolymer and the maleic anhydride monomer.
9. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 2), the temperature of solution polymerization grafting is 110-120°C, and the reaction time is 2-3h.
10. The method for preparing a nylon / polyester compatibilizer according to claim 1, characterized in that: In step 2), the protective gas during solution polymerization grafting is nitrogen or carbon dioxide.